Exploring the application of design elements that combine mixed components with ceramic tea sets / Zhongyue Zuo, Nor Nazida Awang and Rusmadiah Anwar - Zuo, Zhongyue; Awang, Nor Nazida; Anwar, Rusmadiah (Universiti Teknologi MARA, Perak, 2024)
The purpose of this study is to explore the research on the application of design elements by combining multiple materials with ceramic tea sets. This research emphasizes the design elements of combining multiple materials with ceramic tea sets mainly in the analysis and study of material types, process technology, and consumers' aesthetic demands. This project adopts a qualitative research method because it is suitable for studying the innovative elements in contemporary ceramic tea set design, and discovering the visual and technological innovation of integrating comprehensive materials into ceramic tea sets; specifically, this research analyses the application of the design elements of shape, colour, and material in combining multiple materials with ceramic tea sets, and examines the styling principles of ceramic tea set design, the forms of expression, and their influencing factors in this analysis. Research. In general, this study will summarise some useful design principles and development trends for modern ceramic tea set design. It will provide a methodology and theoretical reference for the design of practical ceramic tea ware and hopefully promote the development of ceramic tea ware design. It will be beneficial to designers, researchers, scholars, students, and those interested in research.